A model for predicting low probability of nonsentinel lymph node positivity in melanoma patients with a single positive sentinel lymph node. Issue 6 (27th September 2018) - Bhutiani, Neal; Egger, Michael E.; Stromberg, Arnold J.; Gershenwald, Jeffrey E.; Ross, Merrick I.; Philips, Prejesh; Martin, Robert C. G.; Scoggins, Charles R.; McMasters, Kelly M.
Abstract : Background: Identifying factors associated with nonsentinel lymph node (NSN) metastases in melanoma patients with a single positive sentinel lymph node (SLN) could aid decision making regarding adjuvant therapy. We describe a model for identifying patients with a single positive SLN at low risk for NSN metastasis. Methods: Factors associated with NSN metastasis in patients with a primary cutaneous melanoma and a single positive SLN who underwent completion lymph node dissection (CLND) were identified. These factors were used to construct a model for predicting the NSN status. The model was validated using a separate data set from another tertiary referral cancer center. Results: In the training data set, 111 patients had a single positive SLN. Of these, 27 had positive NSN. SLN tumor deposit diameter ≥0.75 mm (OR, 3.43; P = 0.047), age ≥40 (OR, 12.14; P = 0.024), and multifocal SLN tumor deposit location (OR, 4.16; P = 0.0096) were independently associated with NSN positivity. Patients with 0 to 1 of these risk factors had a low risk of NSN metastasis in both the training (7.5%) and validation (4.6%) data sets. Conclusions: A combination of patient and SLN tumor burden characteristics can help to identify patients with a single positive SLN who are at a low risk of NSN metastasis.